Evaluation of insecticides against mustard aphid, Lipaphis erysimi (Kaltenbach): EVALUATION OF INSECTICIDES AGAINST MUSTARD APHID - D R BAJYA; J LAL; M RANJITH (Journal of Oilseeds Research, 2023)
Field experiments were conducted to evaluate the efficacy of various insecticides against mustard aphid, Lipaphis erysimi on mustard crop during rabi seasons 2020-21 and 2021-22. The results on the field efficacy revealed that performance-wise treatments were in the order of imidacloprid 17.8 SL > thiamethoxam 25%WG> acetamiprid 20%SP > dimethoate 30%EC > malathion 50%EC > fipronil 5%EC > profenofos 50%EC > buprofezin 25%EC. The least population (5.40/plant) of aphid was obtained with application of imidacloprid 17.8% SL at 7 DAS and (6.67/plant) at 10 DAS during 2020-21 and 2021-22, respectively. The same trend was observed till 28th day in comparison to rest of the treatments and untreated control. Significant reduction in population was observed with imidacloprid 17.8 SL @ 27.0 gm a.i./ha followed by thiamethoxam 25%WG @ 25 gm a.i./ha and dimethoate 30%EC @ 200 gm a.i./ha. Imidacloprid and thiamethoxam were significantly superior to other treatments. The maximum yield was obtained with imidacloprid (17.99 and 18.22 q/ha) followed by thiamethoxam (16.62 and 17.37q/ha) during 2020-21 and 2021-22, respectively.